Developing BIM Objects Libraries for Provision of BIM Services: an Action Research - Nguyen, Quan; Nguyen, Hoa Binh; Mai, Vu (International Journal of Sustainable Construction Engineering and Technology, 2024)
Except for the development and operation of a Common Data Environment, BIM applications in projects start with 3D BIM modelling. As one important part of the BIM implementation, 3D BIM modelling is a time consuming task and has a great impact on design accuracy, stakeholder collaboration, then the efficiency of BIM model uses etc. This paper presents an action research in developing BIM objects libraries in an organisation providing BIM services in Vietnam. This research study examined the creation of BIM object libraries for a BIM consultant in Vietnam, emphasizing the challenges encountered during various cycles of the action research conducted. Three cycles of the action research have been completed, resulting in five lessons learned. The findings illustrate the methodology for creating well-organized BIM libraries, which are anticipated to enhance design workflows, increase data consistency, and facilitate seamless information exchange among stakeholders. The insights gained can serve as a valuable reference for both other BIM consultants and the Government in formulating rules, processes, and guidelines to facilitate the adoption of BIM within the Vietnamese construction industry.